THERMODYNAMIC PROPERTIES OF BCC-FE TO MELTING TEMPERATURE AND PRESSURE TO 15 GPA - P. I. Dorogokupets; T. S. Sokolova; K. D. Litasov (Геодинамика и тектонофизика, 2015)
Based on Helmholtz’s free energy, an equation of state of iron (bcc-Fe) is constructed with simultaneous optimization of ultrasonic, X-ray diffraction, dilatometric, and thermochemical measurements in the temperature range from 100 K to the melting points and pressures up to 15 GPa. Calculated thermodynamic functions of bcc-Fe are in good agreement with the reference data and experimental measurements at room pressure, as well as with P–V–T measurements at temperatures up to 773 K and pressures up to 16 GPa. The calculated thermodynamic properties of bcc-Fe (x, a, S, CP, CV, KT, KS, K', GT,P) are tabulated up to 1811 K and 15 GPa. The calculated P–V–T relations for bcc-Fe can be used to calculate pressures at given temperatures and volumes.